2023
DOI: 10.3390/toxics11070574
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Potentially Toxic Elements Pollution and Human Health Risks in Polluted Farmland Soils around Distinct Mining Areas in China—A Case Study of Chengchao and Tonglushan

Abstract: This research study investigates the extent of heavy metal pollution and pollution trends in agricultural soil in mining areas during different time periods. A total of 125 soil samples were collected from two mining areas in China, the Chengchao iron mine and Tonglushan ancient copper mine. The samples were analyzed for various potentially toxic elements (PTEs). The index of geoaccumulation (Igeo), pollution index (Pi), potential ecological risk index (Eri), and hazard index (HI) were calculated to evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
0
0
0
Order By: Relevance
“…The observed concentrations of Cu in this study also exceeded 2 to 10 times the maximum permissible concentrations, reaching 2400 mg/kg. In addition, compared with other areas exposed to copper mining and smelting, the determined concentrations of Cu in our study were significantly higher than those reported in Germany-420.9 mg/kg [18], in Spain-642 mg/kg [56] and in China-1990 mg/kg [57].…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…The observed concentrations of Cu in this study also exceeded 2 to 10 times the maximum permissible concentrations, reaching 2400 mg/kg. In addition, compared with other areas exposed to copper mining and smelting, the determined concentrations of Cu in our study were significantly higher than those reported in Germany-420.9 mg/kg [18], in Spain-642 mg/kg [56] and in China-1990 mg/kg [57].…”
Section: Discussioncontrasting
confidence: 82%
“…27 Al(0.015), 42,43,44 Ca( 42 Ca-0.014; 43 Ca-0.013; 44 Ca-0.015), 54,56,57 Fe( 54 Fe-0.014; 56 Fe-0.015; 57 Fe-0.013), 23 Na(0.017), 24,25,26 Mg( 24 Mg-0.016, 25,26 Mg-0.015), 55 Mn(0.015), 39 K(0.017), 31 P(0.013), 46,47,48,49 Ti (0.012) Determined isotopes of micro-and trace elements *(Oxygen flow rate…”
Section: Analytical Procedures For Ptes Determinationmentioning
confidence: 99%
“…Since mining copper is out of the objective of this paper, the environmental impact and the potential health effects derived from those activities have not been here reviewed. For those interested in that specific issue, the scientific literature contains recent articles where the state-of-the-art has been assessed [14,15,17,22,[62][63][64][65] .…”
Section: Potential Sources Of Human Exposure To Copper: Metallurgy/sm...mentioning
confidence: 99%